Examining the Effect of Endorser Credibility on the Consumers' Buying Intentions: An Empirical Study in Turkey - Ermec Sertoglu, Aysegul; Catlı, Ozlem; Korkmaz, Sezer (International Review of Management and Marketing, 2013)
The purpose of this study is to test whether the source credibility affects buying intention and measure the perceived credibility differences between created spokesperson and celebrity endorser. The influence that endorser credibility dimensions (i.e. attractiveness, trustworthiness and expertise) have on purchase intentions of 326 young consumers has been examined. The results showed that all of the three credibility dimensions for both celebrity endorser and created spokesperson have a positive relationship with purchase intention. Created spokesperson is perceived to be more trustworthy and competent whereas the celebrity endorser is found to be more attractive by the respondents. This study is unique in a way that it covers fairly new and rapidly growing Turkish market. One factor that makes this study unique in Turkey, in which the usage of celebrity endorsers holds significant part in the marketing of products, is the lack of studies that would measure the effectiveness of this method. Keywords: Celebrity endorser; created spokesperson; endorser credibility; buying intention; advertisement JEL Classifications: M31; M37